English vocabulary in use - Redman, Stuart (Cambridge University Press, 2001)
Primarily designed as a self-study reference and practice text, but can also be used for classroom work. Includes 100 easy-to-use units, an answer key, a detailed index with phonemic transcriptions, and illustrations.